Ten Years of Pediatric Lung Ultrasound: A Narrative Review - Musolino, Anna Maria; Tomà, Paolo; De Rose, Cristina; Pitaro, Eugenio; Boccuzzi, Elena; De Santis, Rita; Morello, Rosa; Supino, Maria Chiara; Villani, Alberto; Valentini, Piero; Buonsenso, Danilo (Frontiers in Physiology, 2022)
Lung diseases are the most common conditions in newborn, infants and children and are also the primary causes of death in children younger than 5 years old. Traditionally, lung was not thought to be a target for ultrasound due to their inability to penetrate the gas-filled anatomical structures. With deepening of knowledge on ultrasound in recent years, it is now known that the affected lung produces ultrasound artifacts resulting from the abnormal tissue/gas/tissue interface when ultrasound sound waves penetrate lung tissue. Over the years, the application of lung ultrasound have changed and its main indications in the pediatric population have expanded. This review analyzes the studies on Lung Ultrasound (LUS) in pediatrics, published from 2010 to 2020, with the aim of highlighting the usefulness of pediatric LUS. It also describes the normal and abnormal appearances of the pediatric lung on ultrasound as well as the benefits, limitations and possible future challenges of this modality.